Effect of sugars on production of β-sitosterol from in vitro callus culture of Boerhaavia diffusa L. - Patil, Kapil S.; Bhalsing, Sanjivani R. (Acta Biologica Szegediensis, 2016)
The establishment of friable callus was achieved on Murashige and Skoog (MS) medium fortified with 18 μM of 2,4-dichlorophenoxyacetic acid in combination with 2 μM of 6-benzylaminopurine (BAP). The effect of different sugars such as 3% sucrose, 3% glucose and 3% galactose on the growth of callus tissue and β-sitosterol accumulation was tested. Quantification of β-sitosterol was carried out with the help of high performance liquid chromatography. High growth of callus tissue was observed on MS medium, containing sucrose and glucose as carbon sources and maximum β-sitosterol content was observed in 60 days old callus tissue with 3% glucose as carbon source.